RESPONSIBILITY AS ONE OF INTERNAL PERSONAL DETERMINATION SOCIAL AND COMMUNICATIVE ACTIVITY OF ADOLESCENTS (Pedagogy of Higher and Secondary Education, 2008)
The article is discovered understanding of „responsibility” of teenager's personality in process of touristic activity in the educational process in the comprehensive school